Effects of an Online Education Program on Physical Therapists' Confidence in Weight Management for People With Osteoarthritis: A Randomized Controlled Trial. Issue 4 (12th December 2022) - Allison, Kim; Jones, Sarah; Hinman, Rana S.; Briggs, Andrew M.; Sumithran, Priya; Quicke, Jonathan; Holden, Melanie; Chiavaroli, Neville; Crofts, Sam; George, Elena; Foster, Nadine; Bennell, Kim
Abstract : Objective: To evaluate effects of an online education program about weight management for osteoarthritis on physical therapists' self‐reported confidence in knowledge and skills in weight management and attitudes toward obesity. Methods: In a 2‐group randomized controlled trial, 80 physical therapists (58 female physical therapists) were randomized to education or control groups. The theoretically informed and evidence‐informed online self‐directed training program covered biopsychosocial elements of obesity and weight management. The primary outcome was self‐reported confidence in knowledge in weight management using a customized validated tool (scale 14–70, higher scores indicating higher confidence) assessed at baseline and 6 weeks. Secondary measures included confidence in nutrition care, clinical skills in weight management, and weight stigma. Process measures evaluated participant experience. Differences in change between groups were compared using linear regression models adjusted for baseline scores and stratifying variables (clinical setting; confidence in weight management). Moderation analysis was performed using an interaction approach in a linear regression model and multivariable fractional polynomial interaction approach. Results: A total of 79 participants (99%) completed outcome measures at 6 weeks. The education group demonstrated greater improvement in confidence in knowledge than the control group (adjusted mean difference 22.6 units, 95% confidence interval 19.6, 25.5). Greater improvement in knowledge was associated with lower baseline values (interaction P = 0.002). Secondary outcomes showed greater improvements in confidence in skills and nutrition care and in weight stigma domains favoring the education group. Over 90% of participants would recommend the program to peers. Conclusion: An online education program improves physical therapists' short‐term confidence in knowledge and skills in weight management for people with osteoarthritis and reduces weight‐stigmatized attitudes.